Phenology and production of guava tree cv. “Paluma” pruned at different seasons in Mossoro – RN, Brazil. - Farias, Wagner César; Câmara, Francisco Mickael Medeiros; Pereira, Eduardo Castro; Costa, José Maria; Pereira, Gustavo Alves; Mendonça, Vander (Comunicata Scientiae, 2019)
The pruning allows fruit harvest in different periods, according to the grower decision, being economically viable. The harvest can be scheduled according to the agronomical traits and due to the market price. The experiment was conducted in the didactic orchard of the Federal University of the Semi-Arid Region (UFERSA), from April 2013 to December 2014, in the municipality of Mossoro-RN. It was carried out in a randomized block design, with treatments arranged in a split-plot, which were composed by pruning periods, conducted in April (2013), November (2013) and July (2014). The subplots consisted of pruning intensities (short, medium and long); with four repetitions, where the experimental unit consisted of two plants that was pruned with 8 marked branches. From pruning to harvest, the the following botanical characteristics were evaluated in the marked branches: number of emitted sprouts by branches pruned at the day 15th (NBE); number of established branches by branches pruned at the day 50th (NRE); number of productive branches (NRP); vegetative number (VRN) and the total number of fruits (NFT). The evaluated characteristics presented a significant effect. The long pruning resulted in a higher number of fruits for all evaluated seasons. The best months for pruning was November and July. The guava tree ‘Paluma’ cycle, from pruning to harvest can vary according to the period of pruning, with 132 days in July and 150 days in April.